2012
DOI: 10.1182/blood-2011-12-397919
|View full text |Cite
|
Sign up to set email alerts
|

Btk levels set the threshold for B-cell activation and negative selection of autoreactive B cells in mice

Abstract: On antigen binding by the B-cell receptor (BCR), B cells up-regulate protein expression of the key downstream signaling molecule Bruton tyrosine kinase (Btk), but the effects of Btk up-regulation on B-cell function are unknown. Here, we show that transgenic mice overexpressing Btk specifically in B cells spontaneously formed germinal centers and manifested increased plasma cell numbers, leading to antinuclear autoantibody production and systemic lupus erythematosus (SLE)-like autoimmune pathology affecting kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
165
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 47 publications
15
165
1
1
Order By: Relevance
“…Interestingly, transgenic expression of a BTK hypomorph in an xid background that exhibits 25% of normal expression levels results in the generation of normal numbers of mature B cells but impaired B cell Ab production after immunization (29). Conversely, transgenic overexpression of BTK results in spontaneous germinal center formation, autoantibody production, and SLE-like disease (30). Thus, these results collectively highlight the critical importance of BTK in regulating B cell activation and tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, transgenic expression of a BTK hypomorph in an xid background that exhibits 25% of normal expression levels results in the generation of normal numbers of mature B cells but impaired B cell Ab production after immunization (29). Conversely, transgenic overexpression of BTK results in spontaneous germinal center formation, autoantibody production, and SLE-like disease (30). Thus, these results collectively highlight the critical importance of BTK in regulating B cell activation and tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…Btk mutations in humans cause X-linked agammaglobulinemia (XLA), a severe inherited disease associated with deficiency of B cells in peripheral blood and severely low Ig production. 65 On the other hand, Kil et al 66 demonstrated that transgenic mice that overexpress Btk exhibit spontaneous GCs and large number of plasma B cells, with ANA production and lupus-like autoimmune diseases. Others showed that Btk deficiency was associated with arrest of B-cell development at the pre-B-cell stage.…”
Section: Roles Of Syk and Btk In Sle B Cellsmentioning
confidence: 99%
“…Fluorescent labeling of cell membrane molecules was performed as described previously (21). For isotype-specific staining of intracellular Ig in plasma cells, cells were fixed and permeabilized using Cytofix/Cytoperm Buffer and Perm/Wash Buffer, respectively (BD Biosciences, San Jose, CA), according to the manufacturer's instructions.…”
Section: Flow Cytometry Proceduresmentioning
confidence: 99%
“…We recently observed that overexpression of the BCR signaling molecule Bruton's tyrosine kinase (BTK) restricted to B cells in CD19-hBtk transgenic mice is sufficient to induce an SLE/Sjögren-like disease phenotype (21). Btk protein expression in mouse B cells is normally tightly controlled and upregulated upon BCR stimulation by complex regulatory mechanisms involving micro-RNAs and feedforward NF-kB activation (22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation